Investigating the correlation between demographic and comorbidity profiles with chemotherapeutic toxicity experiences in early-stage breast cancer patients in a private medical oncology practice in South Africa - Minns, Chantelle Pienaar (University of the Witwatersrand, Johannesburg, 2024)
Background: An estimated 24 million people will be diagnosed with cancer globally by 2050, with approximately 16.8 million expected to be residing in low- and middle-income countries. Breast cancer is one of the most prevalent types of cancer diagnosed in women worldwide and 23% of all diagnosed malignancies are attributed to breast cancer. The prevalence of chemotherapy-induced adverse drug reactions ranges globally between a vast 60 - 80% amongst patients, negatively impacting overall treatment outcomes. Aim of study: This study aimed to determine a potential correlation between demographic profiles and the presence of pre-existing comorbidities on the chemotherapy-related adverse effects experienced by patients with stage 0-III breast cancer at a private oncology centre in Gauteng. Furthermore, interventions applied by the oncologists to mitigate the adverse effects were investigated and reported adverse events were compared to the WHO VigiAccess Adverse Drug Reaction database. Methods: A quantitative, retrospective cohort analysis of patient charts from January 2018 to December 2019 at the private Sandton Oncology Centre was undertaken. The study sample size was 54 participants. Patient files were randomly selected. Demographic and comorbidity profiles, as well as the staging (0 – III) data were retrieved from patient medical charts, in accordance with the study inclusion criteria. Furthermore, the chemotherapeutic toxicities, experienced by patients, treated with a particular chemotherapeutic agent were reviewed. Interventions employed to alleviate toxicity were further recorded for data analysis (dose modifications, dose reductions, and premature discontinuation of oncology treatment). Descriptive statistics was analysed using pivot tables in Microsoft Excel. Inferential statistics was analysed with Stata software version 18. Ethical clearance was obtained before patient files were accessed and confidentiality of patient information was maintained throughout the study. Results: Most patients included in the study were white (57.4%), aged 50 – 59 years (29.6%), and diagnosed with stage II breast cancer (48.2%). Most of the patients had tumours which were oestrogen (66.7%) and progesterone positive (57.4%) and Human Epidermal Growth Factor Receptor 2 (HER2) negative (48.2%). The majority of patients, irrespective of ethnicity, received a combination of an anthracycline and cyclophosphamide followed by a taxane (51.8%). The most documented comorbidities were hypertension, obesity, dyslipidaemia, and diabetes. Of those patients reporting adverse effects, 77.8% reported adverse effects after the first cycle of chemotherapy. The chemotherapy-related adverse effects show similarity to the adverse effects reported on the World Health Organisation’s VigiAccess Adverse Drug Reaction database, particularly adverse effects of the digestive, integumentary, haematological and lymphatic systems. Conclusions: The number of comorbidities present increases with age. White patients with more comorbidities experienced more chemotherapy-related adverse effects. The majority of the patients for which dose reductions were implemented, experienced five or more adverse effects during their treatment. More than half of the termination of treatment cases were preceded by a dose reduction. No statistically significant correlation was found between any of the ethnic groups or age categories and the total number of adverse effects experienced. A statistically significant correlation was found between other comorbidities and the number of psychiatric adverse effects (p=0.014). Reported infections were significantly higher in patients with hypertension (p=0.043) and lymphatic system adverse effects were higher in patients with dyslipidaemia (p=0.017)
A Research Report submitted in partial fulfillment of the requirements for the degree of Master of Science in Medicine to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg,Johannesburg, 2024
Keywords: Early-stage breast cancer; Oncology treatments; Chemotherapeutic toxicity; Comorbidities; UCTD; SDG-3: Good health and well-being